How Digital Marketing Empowers the Operation and Development of Physical Stores - Yu, Zhongyi (Transactions on Economics, Business and Management Research, 2024)
This study focuses on the strategy implementation and challenges faced by physical retailers during their digital transformation. By analyzing the digital marketing strategies of well-known companies such as Starbucks, Aroma Home, and Uniqlo, the research provides reference models for other physical retail enterprises undergoing transformation. Utilizing a case study approach, it delves into the specific applications of digital marketing tools and technologies. The results indicate that appropriate use of digital marketing strategies can significantly enhance the market adaptability of physical retailers during their digital transformation, thus boosting their market competitiveness. This research contributes not only to the theoretical study of the retail industry but also offers practical guidelines for physical retail enterprises, facilitating innovation and progress within the retail sector. Consequently, it improves the shopping experience for consumers. In conclusion, physical retailers should refer to the digital marketing strategies of successful enterprises to better adapt to the development trends of the digital era.